Yugo-nostalgia in modern television: Narratives in the show "Šou svih vremena" - Radović, Ognjen (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2015)
After the breakup of Yugoslavia, Yugo-nostalgia is present in the television content primarily in entertainment and informative content (series, movies and news). One of the newest examples of invoking the past and metanarratives connected to Yugoslavia is the variety show “The show of all times” that was aired on RTS (Radio Television of Serbia) and on the other televisions in the region. The paper tries to define the role of nostalgia and narrators and how it is represented the time of Yugoslavia. Second and third level narrators (all except the all-seeing author) are defined as catalysts of Yugo-nostalgia, as those who represent the link between the audience and the time of brotherhood and unity, as moderators (hosts) and as authors-creators of all the narratives in the show and its’ parts (all-seeing authors and the host Nikola Kojo). In fact, they have been used for the purpose of resuscitation and rehabilitation of the narratives of the former Yugoslavia in the present through collective nostalgia. The elements of the metanarrative about former Yugoslavia used in the show are – the free country, a country of brotherhood and unity, the golden age, the time of peace and security, the time of real moral values, the age of innocence, the good old days and the land of plenty. All these elements are describing past time through the spectacle (songs, dance and quiz), humor (sketches, interviews and quiz) and the collective memories of life and popular culture of the former Yugoslavia, positively interpreted and re-positioned the then relations and values.